Manusia dan Teknologi: Perilaku Interaksi Interpersonal Sebelum dan Sesudah Media Digital - Ferdinand Eskol Tiar Sirait (Journal of Education, Humaniora and Social Sciences (JEHSS), 2020)
This article aims to examine the behavior of interpersonal interactions before and after digital media. The method of scientific articles uses descriptive qualitative methods through literature study, namely research based on literature studies and analysis of the development of problems in society. This study concludes that with interpersonal communication a person is more interested, so that creative ideas will grow for self-development. The presence of social media not only has an impact on interpersonal communication but also has an impact on interpersonal relationships. Social media has changed the attitude and style of a person, people who are initially friendly will experience changes to be ignorant of their surroundings because their attention has been diverted to social media. Changes in social relationships or changes as a balance (equilibrium) of social relations and all forms of changes in social institutions within a society, which affect the social system, including values, attitudes and behavior patterns among groups in society. Positive social changes such as obtaining information, obtaining social and economic benefits. Meanwhile, social changes that tend to be negative include social groups acting on behalf of religion, ethnicity and certain behavior patterns that sometimes deviate from existing norms.